Corrosion Inhibitor Patents in Industrial Applications – A Review - Inzunza, R.G.; Valdez, Benjamin; Schorr, Michael (Recent Patents on Corrosion Science, 2013)
Corrosion affects the quality of the environment, the durability of the infrastructure assets and industrial equipments. Therefore, it is crucial using corrosion engineering control methods and techniques, in particular safe
Keywords: water systems